Realism about Indian Higher Education - Altbach, Philip (International Higher Education, 2023)
Indian higher education is opening to the world, but there are many aspects of the world’s second largest system that need to be understood by the global community. A stress on expansion has prevented the emergence of world-class universities. At present, Hindu nationalism and politicization are important forces in India. Academia has traditionally been highly bureaucratic. These are among the underlying realities of one of the key national academic systems in the global landscape.